ChemInform Abstract: Organoborane Catalyzed Regioselective 1, 4‐Hydroboration of Pyridines. Issue 41 (October 2015) - Fan, Xiaoting; Zheng, Junhao; Li, Zhen Hua; Wang, Huadong
Abstract The hydroboration of pyridines, catalyzed by a bulky organoborane, proceeds under metal‐free conditions and shows excellent chemo‐ and regioselectivity.